Pyrogallol-based benzoxazines with latent catalytic characteristics: The temperature-dependent effect of hydrogen bonds on ring-opening polymerization. (May 2018) - Lin, Runsheng; Zhu, Yongfei; Zhang, Yongjian; Wang, Lemeng; Yu, Shujuan
Graphical abstract: Highlights: Two kinds of pyrogallol-based di-benzoxazines are synthesized. The inter- and intramolecular hydrogen bond interactions. Pyrogallol-based di-benzoxazine monomers display latent active catalytic characteristics. Temperature-dependent effect of hydrogen bonds on ring-opening polymerization. Abstract: Two kinds of pyrogallol-based di-benzoxazines (PG-FA and PG-A) with a free phenolic hydroxyl between two oxazine rings attaching to the same benzene were synthesized. The chemical structures of PG-FA and PG-A were identified by 1 H NMR, 13 C NMR and FTIR tests. The ring-opening polymerization (ROP) behavior of PG-FA and PG-A was monitored by DSC, TGA, FTIR and in situ FTIR measurements. The pyrogallol-containing benzoxazines showed latent catalytic activity as they reached melting condition. The inter- and intramolecular hydrogen bonds from the phenolic hydroxyl and oxygen or nitrogen were converted into weak OH⋯π intramolecular hydrogen bonding, which easily released the free phenolic hydroxyl. Then, the free hydroxyl could accelerate the breakage of oxazine ring. The para-position of free phenolic hydroxyl in pygarollol-based benzoxazines was preferentially polymerized with the carbocations. The temperature-dependent evolution of the chemical structure of PG-FA and PG-A on ROP was consistent with the change of hydrogen bonds.